Analysis of the Effect of Expansive Soil Against Deformation in Development Projects Cikampek - Palimanan Sta 166 + 650 Toll Road - Asep Setiawan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
On the pavement of the Cikampek-Palimanan Toll Road, STA 166 + 650, there is predicted deformation due to the influence of the expansive soil underneath. Based on this background, it is necessary to conduct research with the aim of obtaining information on the character and physical properties of the sub grade, so as to determine the type of soil stabilization. From the results of soil identification using the single index method according to Chen, 1988 and Snethen, 1977, if the land at the project site is not replaced (replaced) with land that is not expansive, it will have high swelling potential. The potential for settlement of settlement based on Terzaghi and Peck, namely the amount of reduction of 7.3 cm and the time required for a stable condition or consolidation process occurs for 4.8 months. Force height (total heave) for the original soil conditions is relatively large up to 8.52 cm which causes the pavement of the Cikampek-Palimanan Toll Road to experience deformation.